2015
DOI: 10.1371/journal.pone.0128004
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Community-Acquired Pneumonia with Outpatient Proton-Pump Inhibitor Therapy: A Systematic Review and Meta-Analysis

Abstract: BackgroundProton-pump inhibitors (PPIs) are among the most frequently prescribed medications. Community-acquired pneumonia (CAP) is a common cause of morbidity, mortality and healthcare spending. Some studies suggest an increased risk of CAP among PPI users. We conducted a systematic review and meta-analysis to determine the association between outpatient PPI therapy and risk of CAP in adults.MethodsWe conducted systematic searches of MEDLINE, EMBASE, CINAHL, Cochrane Central Register of Controlled Trials, Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
200
1
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(211 citation statements)
references
References 61 publications
4
200
1
6
Order By: Relevance
“…Respiratory infections such as community acquired pneumonia have been also linked to PPI use. A recent met-analysis of 26 studies reported 49% increase in the risk of community acquired pneumonia, which was at its highest during the first 30 days of PPI initiation [82]. Data also have shown associations between PPIs and increased upper respiratory tract infections and asthma exacerbation in pediatric population [83,95].…”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 99%
“…Respiratory infections such as community acquired pneumonia have been also linked to PPI use. A recent met-analysis of 26 studies reported 49% increase in the risk of community acquired pneumonia, which was at its highest during the first 30 days of PPI initiation [82]. Data also have shown associations between PPIs and increased upper respiratory tract infections and asthma exacerbation in pediatric population [83,95].…”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 99%
“…30 If asymptomatic reflux is suspected, treatment with PPIs is unlikely to ameliorate the symptoms of asthma; if symptomatic reflux is found, a three-month therapeutic trial with PPIs may be reasonable, but if there is no response, the drug should be immediately interrupted. There is a concerning increase in pneumonia 31 and in activity-related bone fractures 32 in children treated with PPIs that calls for a warning in the use of these medications.…”
Section: Making Rational Decisionsmentioning
confidence: 99%
“…[1][2][3][4] Over the last decade, our knowledge of these potential harms has expanded and although some reviewers have concluded that associations may be explained by confounding, 5 other work supports the legitimacy of the earlier safety signals. [6][7][8][9][10] Studies have also emerged more recently reporting other possible serious consequences of PPI use, such as an association with myocardial infarction (MI) and dementia. 11,12 However, further research in these areas is required, to inform our understanding and consequently clarify whether there is a need for us to change PPI prescribing practices.…”
mentioning
confidence: 99%